Studi Kasus–Kelola Paparan Asap Rokok dan Kunjungan Antenatal pada Kejadian Kelahiran Prematur - Kurniasari, Kurniasari; Zachrani, Aliviannisa Hasmah (Jurnal Biomedika dan Kesehatan, 2025)
Background Preterm birth remains one of the leading contributors to infant mortality in Indonesia. In addition, premature infants are more likely to develop diseases. Obstetric factors, such as parity and frequency of antenatal visits, as well as environmental factors, such as exposure to cigarette smoke, can influence the incidence of preterm birth. In Indonesia, parity remains high, and the frequency of antenatal visits varies by region, along with limited understanding of the dangers of second-hand smoke for fetuses. This study aims to analyze the relationship between parity, frequency of antenatal visits, and second-hand smoking, and the incidence of preterm birth. Methods This case-control study included pregnant women aged 20 – 35 years who gave birth to premature and preterm babies between January 2022 and December 2023 in hospitals. Pregnant women with hypertension during pregnancy, antepartum hemorrhage, multiple pregnancies, smoking, alcohol consumption, or postterm gestational age (>42 weeks) at birth were excluded from this study. Data on parity, secondhand smoking history, frequency of antenatal visits in the last pregnancy, and gestational age at childbirth were collected using a questionnaire. Medical records and Maternal – Child Health Books were used to confirm the data collected through questionnaires. The relationships and magnitudes of risk associated with parity, secondhand smoking, and frequency of antenatal care contacts with preterm birth were analyzed using the Chi-Square Test. Results Exposure to cigarette smoke (p=0.036; OR=2.727 [CI: 1.058 - 7.031]) and antenatal visits (p=0.033; OR=4.167 [CI: 1.046 - 16.605]) were associated with the incidence of preterm birth, whereas parity was not associated (p=0.251; OR=1.699 [CI: 0.685 - 4.209]) with the incidence of preterm birth. Conclusions Mothers exposed to cigarette smoke ≥ 5 sticks/day and with non-routine antenatal visits had a 2,727-fold and 4,167-fold increased risk of premature birth.